Identifying differentially expressed genes in goat mammary epithelial cells induced by overexpression of SOCS3 gene using RNA sequencing - Song, Ning; Ma, Cunxia; Guo, Yuzhu; Cui, Shuangshuang; Chen, Shihao; Chen, Zhi; Ling, Yinghui; Zhang, Yunhai; Liu, Hongyu (Frontiers in Veterinary Science, 2024)
Suppressor of cytokine signaling 3 (SOCS3) is a key signaling molecule that regulates milk synthesis in dairy livestock. However, the molecular mechanism by which SOCS3 regulates lipid synthesis in goat milk remains unclear. This study aimed to screen for key downstream genes associated with lipid synthesis regulated by SOCS3 in goat mammary epithelial cells (GMECs) using RNA sequencing (RNA-seq). Goat SOCS3 overexpression vector (PC-SOCS3) and negative control (PCDNA3.1) were transfected into GMECs. Total RNA from cells after SOCS3 overexpression was used for RNA-seq, followed by differentially expressed gene (DEG) analysis, functional enrichment analysis and network prediction. SOCS3 overexpression significantly inhibited the synthesis of triacylglycerol, total cholesterol, nonesterified fatty acids and accumulated lipid droplets. In total, 430 DEGs were identified, including 226 downregulated and 204 upregulated genes, following SOCS3 overexpression. Functional annotation revealed that the DEGs were mainly associated with lipid metabolism, cell proliferation and apoptosis. We found that the lipid synthesis-related genes, STAT2 and FOXO6 were downregulated. In addition, the proliferation-related genes BCL2, MMP11, and MMP13 were upregulated, and the apoptosis-related gene CD40 was downregulated. In conclusion, six DEGs were identified as key regulators of milk lipid synthesis following SOCS3 overexpression in GMECs. Our results provide new candidate genes and insights into the molecular mechanisms involved in milk lipid synthesis regulated by SOCS3 in goats.